Letters to the Editor: Collection of Experiences - Salamanca, Laura Camila; Medina, Yolanda; Carvajal, Angélica María; Mora, Willian Alexander; Rodríguez, Ilba Yaneth; Quintero, Erlenzi; Ramos, Viviana Angélica; Calixto, Lina; Tobar, Mairon Felipe; Impomeni, Andrew Williams; Neisa, Daniela (Universidad Pedagógica y Tecnológica de Colombia, 2020)
A collection of experiences about the current pandemic and language learning and teaching written by students, teachers, and directors.